UM ESTUDO DA QUALIDADE DOS SERVIÇOS BANCÁRIOS EM UMA INSTITUIÇÃO BANCÁRIA DE TRÊS PASSOS - Meinen, Aline F.; Reichert, Miriam I. A.; Gonçalves, Patricia; Schappo, Maria d. L. M.; Zamberlan, Luciano (Salão do Conhecimento, 2013)
Resumo